Developing Strategies for Cultural Tourism Relevant to the ASEAN Community Based on the Creative Economy of Four Dvaravati Provinces - Chantaranamchoo, Nopporn; Rattanapongpinyo, Taninrat; Ratsasanasart, Dechaphan (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
The purpose of this research was to develop strategies for cultural tourism relevant to the ASEAN community based on the creative economy of four Dvaravati provinces . The sampling group of the study consisted of 400 tourists and 58 key informants. A questionnaire, focus group discussion and in-depth interview guide were constructed and used as tools to collect data. Data were analyzed by using descriptive statistics, SWOT analysis and content analysis. The results showed that there were 6 strategies for cultural tourism relevant to the ASEAN community based on the creative economy of four Dvaravati provinces (DVARAVATI strategic plan). They were 1. developing a cluster of four Dvaravati provinces for cultural tourism. 2. developing cultural tourism activity for identity creation and added value. 3. developing four Dvaravati provinces with reliance and alliance for cultural tourism marketing. 4. developing tourism spaces for learning various cultural attractions. 5. developing and training human resources for cultural tourism, and 6. developing integrated marketing communication for the promotion of cultural tourism.